P14 The role of cardiopulmonary exercise testing in assessing anaesthetic risk factors in patients with pulmonary arteriovenous malformations. (December 2018) - Thurairatnam, S; Santhirapala, V; Strangeways, T; Tighe, HC; Perks, J; Jackson, JE; Howard, LS; Shovlin, CL
Abstract : Introduction: Patients with pulmonary arteriovenous malformations (PAVMs) have anatomical intrapulmonary right-to-left shunts that cause low oxygen saturation (SaO2 ). Surprisingly, patients exhibit well-preserved exercise tolerance. As such, they are difficult to assess for anaesthetic risks. Cardiopulmonary exercise testing (CPET) is increasingly recommended to identify high-risk patients pre-operatively, with a focus on the anaerobic threshold (AT). For example, an AT <11 ml min -1 kg -1 has been suggested as 'high-risk' for intra-abdominal surgeries. Methods: Ethically approved research cardiopulmonary exercise tests performed on 26 PAVM patients between April 2011-May 2016 were evaluated for pre-operative risk categories. At least 22 had underlying hereditary haemorrhagic telangiectasia placing them at risk of iron deficiency anaemia. Arterial oxygen content (CaO2 ) in mls oxygen/dL blood was calculated as 1.34 x SaO2 x haemoglobin. STATA was used to perform categorical, univariate and multivariate regression analyses. Results: The median age of patients was 57 years (IQR: 42–66). The AT ranged from 7.6–24.5 ml min -1 kg -1 (median: 12.35; IQR: 9.5–17.35). This placed 11/26 patients in the high-risk AT category. Patients in this category did not have lower SaO2, but did have lower CaO2, haemoglobin, and oxygen pulse, and higher serum bicarbonate. This was robust to alternate categorisation contrasting the 'top 50%' (consisting of 13 patients with AT ranging from 12.6–24.5 ml min -1 kg -1 ) and the 'bottom 50%' group (containing the remaining 13 patients with AT ranging from 7.6–12.1 ml min -1 kg -1 ). Furthermore, in multivariate regression analysis, the inverse relationship with haemoglobin explained 57.3% of the variance in log-transformed AT. The regression coefficient of 0.053 (95% confidence interval 0.005, 0.100, p=0.031) meant for each 1 g/dL (10 g/L) rise in haemoglobin, the AT rose by 0.76 ml min -1 kg -1 . Conclusion: A large proportion of PAVM patients have lower AT that suggest they may be in a hidden high-risk pre-operative risk category. Correcting anaemia, and/or enabling appropriate polycythaemia for hypoxaemic patients may have a benefit in reducing anaesthetic risk. The data suggest CPET may have an important role in anaesthetic assessments for patients with PAVMs. Further study is recommended to develop clinical guidance and potential methods of reducing risk in this patient group.